2011
DOI: 10.1002/chem.201003572
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Base Catalyzed [4+2] Annulation of Electron‐Deficient Chromone‐Derived Heterodienes and Acetylenes

Abstract: Lewis base catalyzed [4+2] annulation reactions between electron-deficient chromone oxa- and azadienes and acetylene carboxylates provide tricyclic benzopyrones inspired by natural products. An asymmetric synthesis of the tricyclic benzopyrones was developed by using modified cinchona alkaloids as enantiodifferentiating Lewis base catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 145 publications
(160 reference statements)
0
25
0
Order By: Relevance
“…Further, authors also reported phenylhydrazones, pyrazole carboxylates and pyrazolyl methanones as biologically active compounds . While research elsewhere reported the synthesis of dihydropyridines, pyrano pyridopyrimidinones, benzopyranopyridinones and tricyclic benzopyrones by the chemical transformation of 3‐formylchromones with the retention of the chromone ring . Similar trend has been observed in synthesis of 2‐hydroxybenzoylpyridones and pyridines by the ring opening of 3‐formylchromone …”
Section: Introductionmentioning
confidence: 52%
“…Further, authors also reported phenylhydrazones, pyrazole carboxylates and pyrazolyl methanones as biologically active compounds . While research elsewhere reported the synthesis of dihydropyridines, pyrano pyridopyrimidinones, benzopyranopyridinones and tricyclic benzopyrones by the chemical transformation of 3‐formylchromones with the retention of the chromone ring . Similar trend has been observed in synthesis of 2‐hydroxybenzoylpyridones and pyridines by the ring opening of 3‐formylchromone …”
Section: Introductionmentioning
confidence: 52%
“…This rearrangement, by analogy, proceeds through pyrylium cations 20 , similar to the transformation of 11 into 12 . In addition, we observed that the N ‐tosyl analogue 22 did not rearrange because the push–pull effect is lacking in this acid‐stable dihydropyridine (Scheme c) 8a…”
Section: Resultsmentioning
confidence: 94%
“…Achiral phosphines such as PPh 3 and PBu 3 can be used for the synthesis of tricyclic benzopyrones 38 through a formal [4+2] annulation reaction depicted in Scheme 21. [39] The phosphine catalyst, according to the aforementioned mechanism, transforms electron-poor acetylenes into nucleophilic zwitterions, which can react in a 1,4-addition to 3-formylchromones 37 to give a stabilized oxanion. This species further undergoes a 1,4-addition to the resulting activated alkenes to liberate the catalyst and deliver the cycloaddition adduct 38.…”
Section: Phosphinesmentioning
confidence: 99%